Biblical Concepts and our World
XI, 283 p.
Keywords: In this collection, distinguished theologians and philosophers of religion explore the relation of key Biblical concepts to our world. They examine a range of concepts, including authority, faith and history, the historical Jesus, the resurrection and miracles.